Modernizing Saudi Arabia's Dates Export Market via Leveraging Technology for Sustainable Growth in the Global Economy - Mohammad Ali Alumushaiti (International Journal of Integrated Science and Technology, 2024)
The dates export market in Saudi Arabia presents both opportunities and challenges for the agricultural sector. This paper examines the current state of the dates market in Saudi Arabia, highlighting key challenges such as water scarcity, climate change, quality control issues, market access barriers, and competition. It explores the role of technology in addressing these challenges and enhancing the competitiveness of Saudi dates in the global market. Various technological advancements, including precision agriculture tools, drip irrigation systems, mechanized harvesting equipment, post-harvest technologies, traceability systems, and digital marketing strategies, are discussed in detail. By leveraging these technologies, Saudi date farmers and exporters can improve productivity, efficiency, quality, and market reach. The paper concludes by emphasizing the importance of strategic investment in technology and innovation to unlock the full potential of the dates export market in Saudi Arabia, driving economic growth and sustainable development in the agricultural sector.